Functional expression and activity screening of all human cytochrome P450 enzymes in fission yeast. Issue 12 (30th May 2019) - Durairaj, Pradeepraj; Fan, Linbing; Du, Wei; Ahmad, Shabir; Mebrahtu, Dawit; Sharma, Shishir; Ashraf, Rana Azeem; Liu, Jiaxin; Liu, Qian; Bureik, Matthias
Abstract : Here, a complete set of recombinant fission yeast strains that coexpress each of the 57 human cytochrome P450 (CYP) enzymes together with their natural human electron transfer partner(s) was cloned. This strain collection was tested with two luminogenic probe substrates, and 31 human CYPs (including the orphan enzymes CYP2A7, CYP4A22 and CYP20A1) were found to metabolize at least one of these. Since other substrates are known for the remaining enzymes, all human CYPs are now shown to be active. Interestingly, CYP5A1 was found for the first time to work on a substrate other than prostaglandin H2, and, moreover, to catalyze an aliphatic hydroxylation reaction that consumes molecular oxygen. Also, the ability of CYP11A1 to catalyze an aryl hydroxylation is another unexpected result. Abstract :